Dietary supplement use among adult survivors of childhood cancer: A report from the St. Jude Lifetime Cohort Study. Issue 10 (17th February 2023) - Zhang, Fang Fang; Hudson, Melissa M.; Chen, Fan; Li, Zhongyu; Huang, I‐Chan; Bhakta, Nickhill; Ness, Kirsten K.; Brinkman, Tara M.; Klosky, James; Ojha, Rohit P.; Lanctot, Jennifer Q.; Robison, Leslie L.; et al.
Abstract: Background: Adult survivors of childhood cancer have poor adherence to nutrition guidelines and inadequate intake of dietary vitamins D and E, potassium, fiber, magnesium, and calcium. The contribution of vitamin and mineral supplement use to total nutrient intake in this population is unclear. Methods: We examined the prevalence and dose of nutrient intake among 2570 adult survivors of childhood cancer participating in the St. Jude Lifetime Cohort Study, and the association of dietary supplement use with treatment exposures, symptom burden, and quality of life. Results: Nearly 40% of the adult survivors of cancer survivors reported regular use of dietary supplements. Although cancer survivors who used dietary supplements were less likely to have inadequate intake of several nutrients, they were also more likely to have excessive intake (total nutrient intake ≥ tolerable upper intake levels) of folate (15.4% vs. 1.3%), vitamin A (12.2% vs. 0.2%), iron (27.8% vs. 1.2%), zinc (18.6% vs. 1%), and calcium (5.1% vs. 0.9%) compared with survivors who did not use dietary supplements (all p < 0.05). Treatment exposures, symptom burden, and physical functioning were not associated with supplement use, whereas emotional well‐being and vitality were positively associated with supplement use among childhood cancer survivors. Conclusions: Supplement use is associated with both inadequate and excessive intake of specific nutrients, but positively impacts aspects of quality of life among childhood cancer survivors. Abstract : Adult survivors of childhood cancer who used dietary supplements were less likely to have inadequate intake of several nutrients but were also more likely to have excessive intake of specific nutrients compared with those who did not use dietary supplements. Health care providers need to monitor dietary supplement use among long‐term survivors of childhood cancer.